1974
DOI: 10.1017/s0033291700042963
|View full text |Cite
|
Sign up to set email alerts
|

Reading ability and brain function: a simple statistical model

Abstract: SYSNOPSISThis report is concerned with a simple statistical model of the way the brain may function, suggested by the analysis of intelligence test results in two groups of children. The model describes the statistical behaviour of an ideal array of elements, representing the brain, during tests of cognitive ability. Predictions from the model indicate that comparison of the EEC recording taken from groups of children who were good or poor readers would show amplitude differences. These were found between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 5 publications
1
23
0
Order By: Relevance
“…This interpretation could account for the increased incidence ofleft and mixed handers in clinic samples and others identified as having a specific problem of speech or reading (Ingram, 1959;Naidoo, 1972;Orton, 1937), and could also account for the absence of reading delays in left and mixed handers in the general population (Clark, 1970). It would be consistent with the absence of a verbal factor in the cognitive test performance of poor readers (Maxwell et al, 1974). For the rs--genotype, the reading problem was expected to arise because, as Brain (1945) put it, the child is without normal hemisphere dominance on either side.…”
Section: Introductionmentioning
confidence: 78%
“…This interpretation could account for the increased incidence ofleft and mixed handers in clinic samples and others identified as having a specific problem of speech or reading (Ingram, 1959;Naidoo, 1972;Orton, 1937), and could also account for the absence of reading delays in left and mixed handers in the general population (Clark, 1970). It would be consistent with the absence of a verbal factor in the cognitive test performance of poor readers (Maxwell et al, 1974). For the rs--genotype, the reading problem was expected to arise because, as Brain (1945) put it, the child is without normal hemisphere dominance on either side.…”
Section: Introductionmentioning
confidence: 78%
“…A number of recent findings suggest that individual differences in cognitive abilities are characterized, in part, by differences in neural efficiency, measured by the amount of brain activation underpinning a given task (e.g., Carpenter, Just, & Reichle, 2000; Haier et al, 1988; Maxwell, Fenwick, Fenton, & Dollimore, 1974; Prat & Just, under revision; Prat, Keller, & Just, 2007). In general, among healthy participants who can perform a task, higher cognitive abilities are indexed by less (more focal distribution or lower intensity) brain activation (see Neubauer & Fink, 2009 for a review).…”
Section: Individual Differences In Neural Efficiencymentioning
confidence: 99%
“…Much of the research on individual differences in comprehension ability has reported increased efficiency in better readers (Maxwell et al, 1974; Prat & Just, under revision; Prat, et al, 2007). Constraints on inference processes may arise, therefore, because less-skilled readers are utilizing more resources for basic comprehension processes, leaving fewer resources available for optional or elaborative processes.…”
Section: Individual Differences In Neural Efficiencymentioning
confidence: 99%
“…Maxwell, Fenwick, Fenton, and Dollimore (1974) were among the first to link cognitive abilities with neural efficiency. In an electrophysiological exploration of good and poor readers, they found evidence that good readers had more efficient neural processes (as indexed by lower power spectra in electroencephalogram) than did poor readers.…”
Section: Introductionmentioning
confidence: 99%